PENERAPAN AKAD MUKHABARAH TERHADAP PENGELOLAAN SAWAH PERSPEKTIF HUKUM ISLAM DI DESA PAJANANGGER KECAMATAN ARJASA KABUPATEN SUMENEP - Hali Makki; Abd. Rahman; Ulfaida (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2022)
The community in Pajanangger Village, Arjasa District, Sumenep Regency, has often seen cooperation in implementing the mukhabarah contract, which they know as Nelon. The agreement is usually carried out orally, without presenting witnesses and does not mention the conditions or pillars that must be met in the contract. The time period for implementing this mukhabarah contract is not clear. In fact, many harvests and years between rice field owners and rice field managers continue to work together for mukhabarah. The collaboration carried out by the community in Pajanangger Village, Arjasa District, Sumenep Regency is Nelon rice field management, namely the application of the implementation of the mukhabarah contract, according to the Islamic Law Perspective, the application of the mukhabarah contract to the management of rice fields in Pajanangger Village, Arjasa District, Sumenep Regency is valid because there has been an agreement from the parties involved. concerned even without having to fulfill certain formalities.